Pencegahan IMS, HIV/AIDS dengan Modul Role Play terhadap Pengetahuan dan Sikap Wanita Pekerja Seksual Langsung - Ani Kuswati; Wahyudi Wahyudi; Rahayu Wijayanti (Jurnal Riset Kesehatan, 2015)
The objective of the research is to evaluate the implementation of Role Play module in the prevention of ISD towards the knowledge and attitude of the female sex workers in Banyumas. The findings show that the numbers of knowledge and attitude  consecutively increase in the intervention group: 2,88 and 2,38. Whereas, in control group it is consecutively increase: 1, 75 and 1, 88. There is a significant improvement of knowledge and attitude after the implementation of the manual role play module in the prevention of ISD among female sex workers (p=0,089 and p=0,433, p less than 0,05). In conclusion, the Role Play module can be used by health workers to  increase the knowledge and attitude of female sex workers in the prevention of ISD.